Five new species of Western Atlantic stardrums, Stellifer (Perciformes: Sciaenidae) with a key to Atlantic Stellifer species - Chao, Ning Labbish; Carvalho-Filho, Alfredo; Santos, Jonas De Andrade (Zootaxa, 2021)
Five new species of Stellifer are described from the Caribbean Sea and tropical southwestern Atlantic. Among the previously recognized stelliferine genera, Stellifer is unique by having a pair of variably developed appendages on the posterior margin of the anterior gas chamber, which is lacking in Bairdiella, Corvula, Elattarchus, Odontoscion and Ophioscion. However, recent genetic studies indicated that Stellifer and Ophioscion are not monophyletic. The genus Ophioscion Gill, 1863 is recognized herein as a junior synonym of Stellifer Oken, 1817. Of the five new species described, Stellifer cervigoni n. sp., S. collettei n. sp., and S. musicki n. sp. have a pair of knob-like diverticula along the posterior margin of the anterior gas chamber, which is absent in S. macallisteri n. sp., and S. menezesi n. sp. Stellifer cervigoni n. sp. is found along the southern Caribbean coast of Colombia and Venezuela; it can be distinguished from other species by having a jet-black roof of mouth and inner opercular lining. Stellifer collettei n. sp. is found from Surinam to southeastern Brazil, while S. musicki n. sp. is endemic to northern Brazil. Stellifer macallisteri n. sp. has an oblique, terminal mouth and it is found in Colombia, Venezuela and Dominican Republic. Stellifer menezesi n. sp. has a subterminal mouth and is found from northeastern to southeastern Brazil. These results bring the number of valid species of Stellifer in the Atlantic to 18, and a key to the identification of these species is included.